Methylome analysis in long-lived men deciphers DNA methylation modifications associated with male longevity in humans - Fu-Hui Xiao; Hao-Tian Wang; Long Zhao; Tian-Rui Xia; Li-Qin Yang; Si-Yu Ma; Qing-Peng Kong (Cell Reports)
Summary: Men, despite having a lower likelihood of longevity compared to women, generally exhibit better health status when they achieve longevity. The role of DNA methylation in this paradox remains unclear. We performed whole-genome bisulfite sequencing on long-lived men (LLMs), long-lived women (LLWs), younger men (YMs) and younger women (YWs) to explore specific methylation characteristics in LLMs. Despite an accelerated methylation aging rate in LLMs compared to LLWs, we identify thousands of differentially methylated genomic units (DMUs) in LLMs independent of age and sex. These DMUs, validated by an elastic net classifier, can serve as methylation markers for discriminating longevity potential in men. Many are located near health-related genes. Genes like PIWIL1 and EXT1, with promoters featuring DMUs, exemplify the potential role of LLM-specific methylation patterns in suppressing age-related diseases by regulating gene transcription. Our findings provide evidence of a distinct methylation feature contributing to healthy aging and longevity of LLMs.